(untitled) (Research, Society and Development, 2022)
Considering the important role of vaccination in controlling the pandemic of COVID-19, as well as the need to maintain the immunogenic characteristics of immunobiologicals, it is necessary to understand the logistical support of the storage and distribution processes of these products. This study aimed to describe the logistical process of distribution of vaccines against COVID-19 within a Regional Health Unit (RHU) of the Jequitinhonha Valley in Minas Gerais. The national vaccination campaign in Minas Gerais began on 01/18/2021. The first batch received by the URS was on 19/01/21 and the entire shipment was distributed to the 25 municipalities under its jurisdiction on 19 and 20/01, with police escort. Considering the current year’s scenario and the arrival of small quantities of vaccines, a vaccine distribution plan was implemented in the state. The logistics proved to be effective for the control of the pandemic in the municipalities under the URS jurisdiction, ensuring agile and systematized distribution and there were no physical losses or exposure of the immunizers to irregular temperatures. The logistics proved to be highly effective in achieving its main objective - to distribute the vaccines in the safest, fastest and most assertive way possible, in order to preserve their effectiveness and immunogenicity to all the municipalities in the shortest possible time, with the aim of making immunobiologicals available and helping to contain the SARS-CoV-2 transmission chain.